2017
DOI: 10.1111/bjdp.12211
|View full text |Cite
|
Sign up to set email alerts
|

Serial order working memory and numerical ordinal processing share common processes and predict arithmetic abilities

Abstract: Recent studies have demonstrated that both ordinal number processing and serial order working memory (WM) abilities predict calculation achievement. This raises the question of shared ordinal processes operating in both numerical and WM domains. We explored this question by assessing the interrelations between numerical ordinal, serial order WM, and arithmetic abilities in 102 7- to 9-year-old children. We replicated previous studies showing that ordinal numerical judgement and serial order WM predict arithmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In the order task, participants have to decide if a sequence is presented in an order or not. Results from previous studies have indicated that there is a strong relation between performance on the order task and arithmetic performance in both children (Attout & Majerus, 2017;Lyons & Ansari, 2015;Lyons et al, 2014;O'Connor et al, 2018O'Connor et al, , 2019Sasanguie & Vos, 2018;Sommerauer et al, 2020;Vogel et al, 2015) and adults (Goffin & Ansari, 2016;Lyons & Beilock, 2009;Morsanyi et al, 2017;Orrantia et al, 2019;Sasanguie et al, 2017;Sella et al, 2020;Vogel et al, 2017Vogel et al, , 2019Vos et al, 2017). However, the mechanisms underlying this relationship remain relatively underspecified.…”
Section: Introductionmentioning
confidence: 99%
“…In the order task, participants have to decide if a sequence is presented in an order or not. Results from previous studies have indicated that there is a strong relation between performance on the order task and arithmetic performance in both children (Attout & Majerus, 2017;Lyons & Ansari, 2015;Lyons et al, 2014;O'Connor et al, 2018O'Connor et al, , 2019Sasanguie & Vos, 2018;Sommerauer et al, 2020;Vogel et al, 2015) and adults (Goffin & Ansari, 2016;Lyons & Beilock, 2009;Morsanyi et al, 2017;Orrantia et al, 2019;Sasanguie et al, 2017;Sella et al, 2020;Vogel et al, 2017Vogel et al, , 2019Vos et al, 2017). However, the mechanisms underlying this relationship remain relatively underspecified.…”
Section: Introductionmentioning
confidence: 99%
“…Renewed interest in symbolic number ordering has emerged following some recent studies, which have shown that number ordering is a stronger predictor of mathematical competence than symbolic number comparison in children from second grade onwards (Lyons, Price, Vaessen, Blomert, & Ansari, 2014;Sasanguie & Vos, 2018) and in adults (Sasanguie, Lyons, De Smedt, & Reynvoet, 2017). Accordingly, several other studies have demonstrated the relationship between symbolic ordering skills and the performance on a mathematical test (Attout & Majerus, 2017;Goffin & Ansari, 2016;Lyons & Ansari, 2015;Lyons & Beilock, 2011Lyons et al, 2014;Morsanyi, Mahony, & Mccormack, 2016;Morsanyi, van Bers, O'Connor, & McCormack, 2018;Rubinsten & Sury, 2011;Sasanguie & Vos, 2018;Vogel et al, 2017;Vogel, Remark, & Ansari, 2014;Vos, Sasanguie, Gevers, & Reynvoet, 2017). Moreover, it has been shown that children and adults with dyscalculia perform worse on a symbolic ordering task when compared with controls (Attout & Majerus, 2014;De Visscher, Szmalec, Van Der Linden, & Noël, 2015;Kaufmann, Vogel, Starke, Kremser, & Schocke, 2009;Morsanyi et al, 2018;Rubinsten & Sury, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although it appears that numerical ordering skills become particularly important from around the age of 6 or 7 (Attout & Majerus, ; Lyons, Price, Vaessen, Blomert, & Ansari, ; Sasanguie & Vos, ), there is also now emerging evidence in support of a role of nonnumerical ordering in mathematical development in the case of younger children (Attout, Noël, & Majerus, ; Morsanyi, van Bers, O'Connor, & McCormack, ; O'Connor, Morsanyi, & McCormack, ). Nonnumerical order processing measures can be broadly divided into two categories: those involving the retrieval of a familiar sequence from long‐term memory, such as the order of familiar daily events, familiar everyday sequences, the months of the year, or letters (Morsanyi, O'Mahony, & McCormack, ; O'Connor et al, ; Sasanguie, De Smedt, & Reynvoet, ; Vos, Sasanguie, Gevers, & Reynvoet, ), and those involving the retrieval of a novel, arbitrary sequence from short‐term memory (order working memory [WM] task; Attout & Majerus, , ; Attout et al, ). O'Connor et al () found that both numerical and nonnumerical ordering measures were related to early mathematical achievement in 4–5‐year‐old children.…”
Section: Table Showing the Results Of Three Longitudinal Studies Regamentioning
confidence: 99%